Calorimetric Study of Helix aspersa Maxima Hemocyanin Isoforms - Svetla Todinova; Yuliana Raynova; Krassimira Idakieva (Journal of Analytical Methods in Chemistry)
The thermal unfolding of hemocyanin isoforms, β-HaH and αD+N-HaH, isolated from the hemolymph of garden snails Helix aspersa maxima, was studied by means of differential scanning calorimetry (DSC). One transition, with an apparent transition temperature (Tm) at 79.88°C, was detected in the thermogram of β-HaH in 20 mM HEPES buffer, containing 0.1 M NaCl, 5 mM CaCl2, and 5 mM MgCl2, pH 7.0, at scan rate of 1.0°C min−1. By means of successive annealing procedure, two individual transitions were identified in the thermogram of αD+N-HaH. Denaturation of both hemocyanins was found to be an irreversible process. The scan-rate dependence of the calorimetric profiles indicated that the thermal unfolding of investigated hemocyanins was kinetically controlled. The thermal denaturation of the isoforms β-HaH and αD+N-HaH was described by the two-state irreversible model, and parameters of the Arrhenius equation were calculated.